2012
DOI: 10.1152/jn.00132.2012
|View full text |Cite
|
Sign up to set email alerts
|

The role of the right presupplementary motor area in stopping action: two studies with event-related transcranial magnetic stimulation

Abstract: The role of the right presupplementary motor area in stopping action: two studies with event-related transcranial magnetic stimulation. J Neurophysiol 108: 380 -389, 2012. First published April 18, 2012 doi:10.1152/jn.00132.2012.-Rapidly stopping action engages a network in the brain including the right presupplementary motor area (preSMA), the right inferior frontal gyrus, and the basal ganglia. Yet the functional role of these different regions within the overall network still remains unclear. Here we focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 84 publications
4
60
0
Order By: Relevance
“…Whereas the studies discussed above used prolonged TMS that preceded the task, Cai et al (2012) demonstrated that also event-related TMS (dual-pulse shortly after the go stimulus) directed at preSMA resulted in longer SSRTs. Using prolonged TMS, Watanabe et al (2015) showed again that the low-frequency variety impaired stopping, whereas the high-frequency variety (known to generally boost neural functioning) actually improved it.…”
Section: Dissociations Between Stop N1 and Stop P3mentioning
confidence: 99%
“…Whereas the studies discussed above used prolonged TMS that preceded the task, Cai et al (2012) demonstrated that also event-related TMS (dual-pulse shortly after the go stimulus) directed at preSMA resulted in longer SSRTs. Using prolonged TMS, Watanabe et al (2015) showed again that the low-frequency variety impaired stopping, whereas the high-frequency variety (known to generally boost neural functioning) actually improved it.…”
Section: Dissociations Between Stop N1 and Stop P3mentioning
confidence: 99%
“…We applied reversible disruption to the right pre-SMA and the rIFG separately by using offline transcranial magnetic stimulation (TMS) to examine how participants' performance in the conditional stop-signal task would be affected as a result of the temporary perturbation of neural activity in the two regions. TMS has been shown to impair performance on a stop-signal task as indicated by an elevated SSRT when it was applied over the pre-SMA [10,37] and over the rIFG [8,7]. Specifically, we wanted to compare the TMS effect on performance in the high-and low-slowing participants.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting that global inhibition mechanisms are not only involved when all motor responses must be suppressed but also for selective inhibitory control, Badry et al (2009) observed a reduced motor evoked potentials of leg muscles in successful stop trials during a manual Stop Signal Task (SST; see also e.g. Cai et al, 2012or Macdonald et al, 2012 for supporting data).…”
Section: Introductionmentioning
confidence: 93%